(3GdefJbi ef cJGH MSf GdXf HGddgs - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s
(3ChdgG (B:s
(3Yf bJGOI Yf QShd Gddg Udi Gddg Ydjg hSde bGd bGd Gddg JYGdi ddedGFcI CdG CNHQJce Yf YHO Hfi ESQGFjd CjG s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B:- ( (3ddg eGFI QMeI hEfeG CfRd efgG QMeI hGMOI Hjf GdLf hGdCfS hGdHgGFe hGdghGe ajgG jJYGWahf hHgG jJQGMehf hHgG JYWa GdhMhT Ydi ChdGOgG hGONQ JSYI hJSYhf QMeI djQMe HgG YHGOg jhe GdbjGeI (B) (3Je GdefJbG ef cJGH MSfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3EfJbGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
Keywords: (3GdJUha hGdBOGH GdTQYjIs